Apa-I polymorphism in VDR gene is related to metabolic syndrome in polycystic ovary syndrome: a cross-sectional study - Santos, Betânia Rodrigues (Reprod Biol Endocrinol, 2018)
BACKGROUND: Polycystic ovary syndrome (PCOS) is a common endocrine disorder determined by polygenic traits as well as environmental factors. Lower vitamin D levels have been detected in PCOS women and related to hormone and metabolic disturbances. Vitamin D acts in tissues through the vitamin D receptor (VDR). VDR gene variants have been associated with worse metabolic profile in the general population. We investigated the genotype and haplotype distribution of the Bsm-I (rs1544410), Apa-I (rs7975232), and Taq-I (rs731236) VDR gene polymorphisms in PCOS and non-hirsute women from southern Brazil. We further investigated the associations of these gene variants and their haplotypes with PCOS, vitamin D levels, and metabolic abnormalities, including the metabolic syndrome (MetS). METHODS: A group of 191 women with PCOS (Rotterdam criteria) and 100 non-hirsute controls with regular ovulatory cycles were genotyped for all polymorphisms by real-time PCR, with allelic discrimination assays. MetS and the cutoffs for its isolated components were defined in accordance with the Joint Scientific Statement. RESULTS: Women with PCOS were younger and had significantly higher BMI and total testosterone levels than controls (p < 0.05). The frequency of MetS in PCOS and controls was 26.5% and 4.8% respectively. The CC genotype of Apa-I entailed higher risk of MetS in PCOS (OR: 2.133; 95% CI 1.020–4.464, p = 0.042), and was associated with higher systolic blood pressure (p = 0.009), total cholesterol (p = 0.040), and LDL-cholesterol (p = 0.038) in both PCOS and control groups (two-way ANOVA). The frequencies of VDR haplotypes were similar in PCOS and control women. CONCLUSIONS: The present results suggest that the Apa-I variant in VDR gene may be associated with MetS in southern Brazilian women with PCOS, and with blood pressure, total cholesterol, and LDL-c in women with and without PCOS.